Iridium-catalyzed enantioselective reductive amination of aromatic ketones. Issue 16 (6th August 2020) - Liu, Ruixia; Li, Bin; Han, Jingkuo; Zhang, Dongxu; Li, Muqiong; Yao, Lin; Zhao, Wei; Wang, Qiaofeng; Jiang, Ru; Nie, Huifang
Abstract : A highly efficient catalytic system of direct asymmetric reductive amination of aromatic ketones. Abstract : A highly efficient direct asymmetric reductive amination of aromatic ketones catalyzed by an iridium complex of Josiphos-type binaphane ligands was described. This concise and practical method provided chiral amines in high yields and enantioselectivities (up to 99% ee).